A Critical Appreciation of Abū al-A‘lā al-Mawdūdī’s Reading of Sufism - Muhammad Maroof Shah (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2020)
There is a problem of persistence of anti-Sufi image of Syed Abū al-A‘lā al-Mawdūdī owing its genesis partly to tangential engagement with key doctrinal issues of Sufism and certain ambivalence regarding it in him and, more significantly, due to Mawdūdī’ scholarship’s atomistic reading of his key statements. For addressing this key problem, this paper critiques atomistic reading and explores certain background methodological issues and reflections on definitions of Sufism besides key points in his life and work. Our analysis of his work shows he entered into a dialogue with Sufism, acknowledged his debt to it, and we better approach him a contributor to the debate on Sufism and not its simplistic denier/outsider. Evidences include, among others, his moral mysticism, his respect for major Sufi Masters and celebration of his Sufi ancestry, his attempt to visit Sufi Masters, his early poetry in Sufi vein, his involvement with (and influence from) the al-Asfār al-Arba‘a of Mulla Sadra, and his reworking/appropriation of certain key Sufi themes and Sufi organizational structure in the Jamaat-e-Islami.